Superiority of Mesoporous Silica-Based Amorphous Formulations over Spray-Dried Solid Dispersions - Hongwei Zhang; Minglu Li; Jianmin Li; Anjali Agrawal; Ho-Wah Hui; Demin Liu (MDPI AG, 2022)
The aim of this study was to compare the performance of two amorphous formulation strategies: mesoporous silica via solvent impregnation, and solid dispersions by spray drying. Poorly soluble fenofibrate was chosen as the model drug compound. A total of 30% Fenofibrate-loaded mesoporous silica and spray-dried solid dispersions (SDD) were prepared for head-to-head comparisons, including accelerated stability, manufacturability, and in vitro biorelevant dissolution. In the accelerated stability study under 40 °C/75% RH in open dish, mesoporous silica was able to maintain amorphous fenofibrate for up to 3 months based on solid-state characterizations by PXRD and DSC. This result was superior compared to SDD, as recrystallization was observed within 2 weeks. Under the same drug load, fenofibrate-loaded mesoporous silica showed much better flowability than fenofibrate-loaded SDD, which is beneficial for powder handling of the intermediate product during the downstream process. The in vitro 2-stage dissolution results indicated a well-controlled release of fenofibrate from mesoporous silica in the biorelevant media, rather than a burst release followed by fast precipitation due to the recrystallization in the early simulated gastric phase for SDD. The present study demonstrates that mesoporous silica is a promising formulation platform alternative to prevailing spray-dried solid dispersions for oral drug product development.